Recombinant Potyvirus lilimaculae in asymptomatic Galanthus nivalis: Ecological and evolutionary implications - János Ágoston; Asztéria Almási; Katalin Salánki; László Palkovics (PLoS ONE, 2026)
Snowdrops are economically important early-spring flowering geophytes. They are protected both in Hungary and across the European Union, and their international trade is regulated under the Washington Convention. Despite their importance, virological research on Galanthus species and cultivars remains limited. To date, only a single virus, Snowdrop virus Y, a tentative member of the genus Potyvirus within the family Potyviridae, has been identified in Galanthus . In this study, ten wild leaf samples and one cultivated, asymptomatic leaf samples were collected in accordance with the prescribed permit conditions. Both ELISA and RT-PCR tests were conducted, indicating infection by a Potyvirus. Direct sequencing of the PCR products revealed nucleotide heterogeneity in one sample, suggesting infection with multiple isolates of the same virus. In this case, the purified PCR product was ligated into pGEM®-T Easy vector. Individual clones were then sequenced to identify the distinct viral isolates present. A BLAST analysis of the sequences revealed that all three snowdrop isolates shared at least 96% identity in the complete coat protein region with the Potyvirus lilimaculae (lilí mottle virus, LMoV) isolate Handan (JF714974), previously identified in Narcissus tazetta var. chinensis from Hubei Province, China. To confirm pathogenicity, sap inoculation was performed on ELISA- and RT-PCR-negative snowdrops. One year later, these plants were re-tested via the same methods, which confirmed successful infection. Phylogenetic analysis revealed that all snowdrop isolates clustered within subgroup II and presented strong recombination signals. The detection of LMoV in asymptomatic wild plants has major implications for nature conservation, horticulture, virus reservoir identification, phytosanitary regulation, and our understanding of Potyviridae evolution.